2023
DOI: 10.3390/separations10090467
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Removal from Water Sources by Adsorption on MOFs

Athanasia K. Tolkou,
Anastasios I. Zouboulis

Abstract: Fluoride is present in several groundwaters due to natural or anthropogenic origins. Although it is necessary for physiological human functions (in small amounts, i.e., 0.5–1.2 mg/L), it could be very harmful when it exceeds the maximum permissible concentration limit of 1.5 mg/L (according to WHO). Among the numerous technologies for removing fluoride from waters, metal–organic framework (MOF) materials are considered to be promising adsorbents due to their advantages of high porosity, high specific surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…The results of the present work under optimal experimental conditions (298 K temperature, 2 h contact time, and pH 7) confirmed that the proposed sorbents with a low dose of 0.8 g/L enable efficient removal of fluoride ions with removal efficiencies 92.93, 95.59, and 98.61% for the synthesized alumina NPs, NiO NPs, and alumina/NiO NCS, respectively. The experimental conditions of the present work are consistent with the other described methods with respect to the Langmuir adsorption isotherm model. The advantage of the current method is that the removal efficiency can be carried out in a wide pH range of 2–8.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present work under optimal experimental conditions (298 K temperature, 2 h contact time, and pH 7) confirmed that the proposed sorbents with a low dose of 0.8 g/L enable efficient removal of fluoride ions with removal efficiencies 92.93, 95.59, and 98.61% for the synthesized alumina NPs, NiO NPs, and alumina/NiO NCS, respectively. The experimental conditions of the present work are consistent with the other described methods with respect to the Langmuir adsorption isotherm model. The advantage of the current method is that the removal efficiency can be carried out in a wide pH range of 2–8.…”
Section: Resultsmentioning
confidence: 99%